2022
DOI: 10.1111/vox.13240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on blood donor deferral patterns during the COVID‐19 pandemic: A retrospective analysis

Abstract: Background and Objectives Blood donor deferral is an essential tool for blood safety. The ongoing COVID‐19 pandemic has adversely affected blood transfusion services all over the world. But its impact on donor deferral rate and the pattern is unclear in light of the new donor deferral policy due to the COVID‐19 pandemic. Materials and Methods This retrospective study was divided into pre‐COVID and COVID (15 March 2019–14 March 2021). All the deferred donors were divided into six different categories: (1) medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…18 In one study, it was found that older adults delayed blood donation mostly because of medical problems. 14 In the present study, the blood donation status of male students was found to be significantly higher (Table 5).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…18 In one study, it was found that older adults delayed blood donation mostly because of medical problems. 14 In the present study, the blood donation status of male students was found to be significantly higher (Table 5).…”
Section: Discussionsupporting
confidence: 41%
“…6,7,10 In a retrospective study, it was determined that while blood donations were delayed due to drugs and vaccination before the pandemic, they were delayed mostly due to the flu and similar symptoms during the pandemic period. 14 The periods of lockdowns due to the pandemic, the time required for blood donation, and the lack of trust have led to a decrease in blood donation. 15 In the study, it was determined that the rate of students donating blood decreased significantly before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly for blood banks, this pandemic generated shortages of blood components, forcing staff to change their donation promotion actions and the dynamics of accepting blood donors to protect patients from COVID-19. As it was a new disease, its infectious capacity by transfusion was unknown, so other reasons for donors’ rejection such as respiratory diseases, COVID-19 vaccine or contact with positive patients were included in the selection protocol [ 12 , 13 ]. However, in Colombia the impact of the COVID-19 pandemic on the seroprevalence of these infections, and their interaction with other risk factors has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Donor deferral policies based on exposure risk, COVID-19 disease and travel were also introduced by blood operators [ 93 ]. Decreases in blood donations prompted blood operators to consider strategies and approaches to improve donor recruitment [ 45 , 94 , 95 ]. The introduction of COVID-19 vaccines required blood operators to review the characteristics of each vaccine and determine if donors should be deferred after vaccine as well as the duration of any deferral periods [ 96 ].…”
Section: How Blood Operators Can Prepare For the Next Pandemicmentioning
confidence: 99%